2017
DOI: 10.1002/2017jd027287
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Viability of Airborne Bacteria Over the Kuroshio Extension Region in the Northwestern Pacific Ocean: Data From Three Cruises

Abstract: Airborne bacteria have been shown to act as condensation and ice nuclei in mixed‐phase clouds and are consequently hypothesized to have significant effects on atmospheric processes and even the global climate. However, few data are available regarding their concentration and variation in the air over the open ocean. Aerosol samples were collected during three cruises in the early summers of 2013, 2014, and 2016 over the Kuroshio Extension region of the northwest Pacific Ocean. The concentrations of viable and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 83 publications
(154 reference statements)
0
22
0
Order By: Relevance
“…Thus, the satellite‐derived concentrations of chlorophyll‐ a alone cannot explain the highest observed values. Hu et al () observed the highest bacterial abundance in the atmosphere on 25 June 2014 near the largest cyclonic eddy, which represents the continuance of the largest cyclonic eddy in April. Bacteria and nutrients may be pushed to the surface by upwelling in cyclonic eddies (Chang et al, ; Hu et al, ; Kouketsu et al, ; Zhang et al, ); afterward, they may rapidly degrade organic matter at the surface (Letscher et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the satellite‐derived concentrations of chlorophyll‐ a alone cannot explain the highest observed values. Hu et al () observed the highest bacterial abundance in the atmosphere on 25 June 2014 near the largest cyclonic eddy, which represents the continuance of the largest cyclonic eddy in April. Bacteria and nutrients may be pushed to the surface by upwelling in cyclonic eddies (Chang et al, ; Hu et al, ; Kouketsu et al, ; Zhang et al, ); afterward, they may rapidly degrade organic matter at the surface (Letscher et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al () observed the highest bacterial abundance in the atmosphere on 25 June 2014 near the largest cyclonic eddy, which represents the continuance of the largest cyclonic eddy in April. Bacteria and nutrients may be pushed to the surface by upwelling in cyclonic eddies (Chang et al, ; Hu et al, ; Kouketsu et al, ; Zhang et al, ); afterward, they may rapidly degrade organic matter at the surface (Letscher et al, ). Recently, organic matter pools consisting of relatively small molecules have been reported in the surface waters of various oligotrophic open oceans (Jennings et al, ; Quinn et al, ; Wurl et al, ; Zäncker et al, ), but the observed concentrations of chlorophyll‐ a in surface water have been low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional microorganisms may have been introduced through sediment that was resuspended by wind and wave action 4,5 . Air-borne contamination during sample handling and filtration were likely low, due to the differences in cell concentration of air (10 3 −10 7 cells m −3 ) 56 and sample water (10 10 -10 11 cells m −3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The flow rate for the BioSampler/holder was 10−12.5 L min -1 , and the collection duration was 1−2 hours. More details on sample collection with the BioSampler and the in-line holder are available in Murata and Zhang (2016) and Hu et al (2017), respectively. The discrepancy between the results of the Andersen sampler and the other two samplers might have been caused by the different sampling durations and collection efficiencies of the samplers (e.g., for the Andersen sampler, there was a loss of bacteria due to bouncing, and the size fraction smaller than 0.43 m was missing).…”
Section: Text S2 Resuspension Of Aerosol Particles In Andersen Samplersmentioning
confidence: 99%